Mexican Bromeliad Weevil (no official common name), Metamasius callizona (Chevrolat) (Insecta: Coleoptera: Curculionidae: Dryophthorinae) - Barbra Larson; J. Howard Frank (EDIS)
Metamasius callizona (Chevrolat) has no official common name but has been referred to as the "Evil Weevil" by bromeliad enthusiasts throughout Florida, as a result of the destruction it has caused to native populations of bromeliads in the southern portion of the state. A member of the weevil subfamily Rhynchophorinae, it is one of three species of the genus Metamasius present in Florida. Metamasius mosieri Barber, the smallest of the three and native to Florida, Cuba, and the Dominican Republic, has been collected in Florida infrequently. Unlike M. callizona, its presence does not threaten populations of native bromeliads in Florida's natural areas. The third species, Metamasius hemipterus (L.), was first reported in Florida in Miami-Dade County in 1984 and has since become an important pest of sugarcane, bananas, and ornamental palms. This document is EENY-161, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000.